Digitalizing HR Management in Preschools: An Analysis of Digital Platforms for Tracking Educator Performance and Portfolios (Journal of Pedagogical Inventions and Practices, 2025)
The realm of early childhood education has experienced considerable transformation in recent years. One of the most significant shifts relates to the integration of digital platforms into human resource management within preschools. As educational institutions strive for greater efficiency, transparency, and effectiveness in all operations, the adoption of digital tools for tracking educator performance and maintaining comprehensive portfolios has become increasingly relevant. The growing complexity of professional requirements and administrative responsibilities necessitates innovative approaches, and digitalization offers a spectrum of possibilities to address these modern challenges.